Women, regional radio and development: the role of north upper Egypt radio in the struggle of females towards development in North Upper Egypt - Rahman, Haidi M. K. Abdel (AUC Knowledge Fountain, 2010)
This study examines the role of regional media in development. Using North Upper Egypt as an example, the thesis illustrates how a regional medium with a development mission might be able to contribute to the development of women in North Upper Egypt. The thesis inquiry required the search for more information than published about Egyptian radio stations. It also surveys the role of North Upper Egypt Radio Station in developing rural and urban female listeners at all levels.